Application of intraoperative lung-protective ventilation varies in accordance with the knowledge of anaesthesiologists: a single-Centre questionnaire study and a retrospective observational study - Seung Hyun Kim (BMC Anesthesiology, 2018)
Abstract Background The benefits of lung-protective ventilation (LPV) with a low tidal volume (6 mL/kg of ideal body weight [IBW]), limited plateau pressure (< 28–30 cm H2O), and appropriate positive end-expiratory pressure (PEEP) in patients with acute respiratory distress syndrome have become apparent and it is now widely adopted in intensive care units. Recently evidence for LPV in general anaesthesia has been accumulated, but it is not yet generally applied by anaesthesiologists in the operating room. Methods This study investigated the perception about intraoperative LPV among 82 anaesthesiologists through a questionnaire survey and identified the differences in ventilator settings according to recognition of lung-protective ventilation. Furthermore, we investigated the changes in the trend for using this form of ventilation during general anaesthesia in the past 10 years. Results Anaesthesiologists who had received training in LPV were more knowledgeable about this approach. Anaesthesiologists with knowledge of the concept behind LPV strategies applied a lower tidal volume (median (IQR [range]), 8.2 (8.0–9.2 [7.1–10.3]) vs. 9.2 (9.1–10.1 [7.6–10.1]) mL/kg; p = 0.033) and used PEEP more frequently (69/72 [95.8%] vs. 5/8 [62.5%]; p = 0.012; odds ratio, 13.8 [2.19–86.9]) for laparoscopic surgery than did those without such knowledge. Anaesthesiologists who were able to answer a question related to LPV correctly (respondents who chose ‘height’ to a multiple choice question asking what variables should be considered most important in the initial setting of tidal volume) applied a lower tidal volume in cases of laparoscopic surgery and obese patients. There was an increase in the number of patients receiving LPV (VT < 10 mL/kgIBW and PEEP ≥5 cm H2O) between 2004 and 2014 (0/818 [0.0%] vs. 280/818 [34.2%]; p <  0.001). Conclusions Our study suggests that the knowledge of LPV is directly related to its implementation, and can explain the increase in LPV use in general anaesthesia. Further studies should assess the impact of using intraoperative LPV on clinical outcomes and should determine the efficacy of education on intraoperative LPV implementation.